2020
DOI: 10.3390/cancers13010108
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Ovarian Cancer Susceptibility

Abstract: Epigenetic alterations are somatically acquired over the lifetime and during neoplastic transformation but may also be inherited as widespread ‘constitutional’ alterations in normal tissues that can cause cancer predisposition. Epithelial ovarian cancer (EOC) has an established genetic susceptibility and mounting epidemiological evidence demonstrates that DNA methylation (DNAm) intermediates as well as independently contributes to risk. Targeted studies of known EOC susceptibility genes (CSGs) indicate rare, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Secondly, our study also revealed that the abnormally high expression of ARRDC2 may be associated with abnormal hypomethylation of DNA, as shown in Supplementary Figures S2A–D . Numerous studies have confirmed that DNA methylation in epigenetics plays an important role in the malignancy, metastasis and recurrence of ovarian cancer ( Papakonstantinou et al, 2020 ; Reid and Fridley, 2020 ). Epigenetic regulation, represented by DNA methylation, is essential for the regulation of oncogenes ( Oliveira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our study also revealed that the abnormally high expression of ARRDC2 may be associated with abnormal hypomethylation of DNA, as shown in Supplementary Figures S2A–D . Numerous studies have confirmed that DNA methylation in epigenetics plays an important role in the malignancy, metastasis and recurrence of ovarian cancer ( Papakonstantinou et al, 2020 ; Reid and Fridley, 2020 ). Epigenetic regulation, represented by DNA methylation, is essential for the regulation of oncogenes ( Oliveira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of omics sequencing technology has allowed researchers to analyze the mechanism of OV progression through large-scale gene expression data and clinical information. Aberrant DNA methylation is the most widely studied deregulatory epigenetic mechanism in tumors [ 18 ], making it valuable in evaluating OV patients' prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Research into ovarian carcinomas has recognized characteristic hypomethylation in Sat2 [ 244 , 245 ]. Moreover, ovarian cancer cells were found to have a reduced LINE-1 methylation phenotype corresponding to the global methylation and hypermethylation of specific gene sites such as the BRCA1 promoter [ 246 , 247 , 248 ].…”
Section: Egcg Treatment In Malignant Gynecological Diseasesmentioning
confidence: 99%